O discurso publicitário da marca Barbie: a produção de sentidos e a representação das mulheres - Da Cas, Dayane (2023)
The meaning and complexity of the discourses are situated and understood under social, cultural and political aspects. Thus, the interpretation of a brand's discourse, for example, is capable of identifying values and perceptions. In the present research, we highlight the communication of the Barbie brand, in which, over the years, especially from 2015, some discursive changes in the advertising intention and in the communication tone have been observed, with regard to issues of gender, race and class Social. In addition, the focus given to female empowerment for the construction of a new social and identity positioning of the brand stands out. We seek to map, through cartography, advertising pieces and documents that engender the discursive trajectory of the Barbie brand. And we ask ourselves: From the 90's, how were women represented in the Barbie brand, considering the discursive values and also the social, historical and political context? Therefore, the objective was to understand and verify which values are present in the contemporary discursive narrative of the Barbie brand, analyzing the use of the social cause as a strategy for the production of meanings, in addition to questioning how the brand's values are integrated with the issues of feminism and of social reality. For this, mainly documental pieces were selected from the 90's, including reports, advertisements, denouncements registered in publicity regulatory bodies; records of communicational actions; audiovisual pieces and images of the brand's dolls on store shelves. Each of the attention phases of Cartography (tracking, touching, landing and attentive recognition) proposed by Kastrup (2006) corresponds to a data collection technique and a specific data set. The audiovisual pieces collected were analyzed from the categories of Semprini's Semiotic Mapping (1995). With this procedure, it was possible to identify different meanings and values present in the brand discourse in a discursive trajectory. Thus, we found current argumentative sources of Barbie's discourse: the presence of “actors” aligned with the projection of a future full of happiness and success, the feeling of acceptance of one's own body and the stimulus to achieve and fight for dreams; and also the perspective under the strategic content and commercial interest. As a main result, we built a rhizome from points and values that mark the discursive trajectory of the Barbie brand. Contextualizing the importance of building the advertising discourse, especially aimed at children, and understanding the alignment of the brand's communication efforts and the use of social causes for its strategic purposes, allows us to perceive the process of the trajectory of an advertising discourse and his attempt to align himself with the spirit of the time.